2018
DOI: 10.12669/pjms.346.15663
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Bad News: A contextual model for Pakistan

Abstract: Objectives:The purpose of the study was to identify the sequence of violence that ensues after breaking bad news and develop a contextual model of breaking bad news and develop a model contextual for Pakistan.Methods:A qualitative exploratory study was conducted using Six FGDs and 14 IDIs with healthcare providers working in the emergency and the obstetrics and gynecology departments of tertiary care hospitals of Karachi, Pakistan. Data was transcribed and analyzed to identify emerging themes and subthemes usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…To our knowledge, the current study is the first study of its kind in Egypt. Breaking bad news is a common volatile situation that is potentially violence and require certain skills and approach to communicate and prevent its escalation into violence against HCPs [ 25 ]. This highlights the importance of conducting this training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the current study is the first study of its kind in Egypt. Breaking bad news is a common volatile situation that is potentially violence and require certain skills and approach to communicate and prevent its escalation into violence against HCPs [ 25 ]. This highlights the importance of conducting this training.…”
Section: Discussionmentioning
confidence: 99%
“…understanding trauma, neuroscience of threat and safety can help HCPs in understanding patients’ aggression and develop strategies to better cope with it [ 24 ]. Breaking bad news is a common volatile situation that is potentially violence and require certain skills and approach to communicate and prevent its escalation into violence against HCPs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some literature has appeared over the last decade. This provides a contextual model for the subject [18] . The findings of Baig et al included a general recognition of the value of presenting bad news among clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Pakistan explored the causes of violence against HCPs. The HCPs from different categories perceived impatience, lack of respect towards HCPs, unrealistic expectations from HCPs and hospital as the client related factors and bad attitude of HCPs towards patients and caretakers, lack of timely communication, inability to counsel caretakers and prepare for undesirable outcomes as the provider-related factors for the violence against HCPs [ 6 ]. The Italian parents perceived that their role as parents and the physical intimacy were compromised during the PICU period.…”
Section: Discussionmentioning
confidence: 99%
“…The efforts, attitude, behaviour and communication by the HCPs have impact on the acceptance and response from the parent and family. While in majority of the instances, the parents and family accept the bad news, there are instances of unpleasant reactions and violence against the HCPs and hospitals [ 6 ]. A study from India reported families dissatisfaction with the services, miscommunication and ineffective communication and death as the important reasons following the non-availability of medicines, facilities and manpower challenges in healthcare services [ 7 ].…”
Section: Introductionmentioning
confidence: 99%